Numerical investigation of pulsating flow structures and heat transfer enhancement performance in spherical corrugated helical tube. (August 2022) - Li, Yaxia; Yu, Qingping; Yu, Sanchuan; Gong, Bin; Zhang, Jing
Graphical abstract: Highlights: Pulsating flow benefits heat transfer of helical tube with spherical corrugation. Flow field and local heat transfer characteristic of a pulsating cycle are analyzed. Optimum dimensionless pulsating frequency for thermal performance is Wo  = 35. Overall thermal performance parameter TP is in the range of 1.06–1.13. Abstract: In this study, the innovative technology of a square wave pulsating flow combining with a spherical corrugated wall structure was applied in a helical tube to enhance heat transfer. Subsequently, the unsteady flow structure and heat transfer characteristics were numerically investigated. The accuracy of the numerical results was verified using experimental data and results in the open literature. For constant values of the geometrical parameters of the spherical corrugated helical tube, the effects of pulsating parameters on the heat transfer enhancement performance were explored, including dimensionless frequency ( Wo ) and dimensionless amplitude ( A ¯ ). The results indicated that the disturbance induced by the pulsating flow improved the local flow field inside the spherical corrugation. In addition, the intensity of the secondary flow and the turbulent kinetic energy of mainstream were simultaneously enhanced. Further, during more than 60% of one pulsation period, the average Nusselt number ( Nu m ) was noticeably greater than that in steady flow with the same average velocity. The maximum value of Nu m occurred at the end of the first half cycle and was increased by 38.5%. The optimum dimensionless pulsation frequency was Wo  = 35 within the studied range. The Nusselt number and the friction factor increased with increase in the dimensionless amplitude. However, the comprehensive heat transfer enhancement performance was better under smaller A ¯ value. Furthermore, within the scope of the Dean number ( De ) De  = 2936–4894, the overall thermal performance ( TP ) parameter was in the range of 1.06–1.13.